Study on compressive stress relaxation behavior of beech based on the finite element method - Gang Hu, Wen; Yuan Guan, Hui (Maderas. Ciencia y Tecnología, 2019)
The compressive stress relaxation behaviors in three directions of beech (Fagus orientalis) were studied by experiments, and predicted by mechanical model and finite element method. Firstly, short-term (3 hours) compressive stress relaxation experiments were carried out in longitudinal (L), radical (R) and tangential (T) directions of beech, and then the experimental data was fitted by mechanical model with two single Maxwell bodies in parallel connection. Secondly, the method of predicting the long-term (12 hours) stress relaxation behaviors of beech based on the finite element method was studied using the experimental data of short-term stress relaxation. Finally, the long-term stress relaxation behaviors in three directions of beech were investigated by experiments, mechanical model and finite element method respectively, and the results of them were compared. The results showed that stress relaxation behaviors of beech were different in three directions, and the short-term stress relaxation in L was much smaller than those in R and T directions under the same load. Besides, the mechanical model with two single Maxwell bodies in parallel connection was able to be predict the short-term relaxation behaviors of beech in three directions with correlation coefficients beyond 0.99, but it did not work in long-term relaxation. In addition, the errors of FEM were smaller than those of the mechanical model compared with the results of experiments in the long-term stress relaxation, and the errors of the FEM were approximately 8% in L and 20% in R and T directions, which were all accepted in the field of wood engineer. This study will contributes to predict the long-term relaxation behaviors of wood products and wooden structures based on the FEM.